The Relevance of the Traditional Malay Islamic Curriculum Towards Strengthening the Values of Responsibility and Discipline in Elementary School Students - Jami'atul Husna; Nyayu Soraya; Baldi Anggara (Journal of Educational Sciences, 2026)
The traditional Malay Islamic curriculum embodies noble values that emphasize the balance between knowledge, manners, and good deeds. In the context of modern primary education, these values are relevant for strengthening students' character, particularly in terms of responsibility and discipline. This study aims to analyze the relevance of the traditional Malay Islamic curriculum to strengthening the character values of elementary school students. The research method used is library research with a descriptive qualitative approach. Data sources consist of primary and secondary literature in the form of books, journal articles, and educational policy documents. The results of the study indicate that Malay Islamic values such as manners, trustworthiness, religious discipline, and social responsibility contribute significantly to the formation of children's character. This curriculum positions teachers as role models and education as a process of spiritual and social habituation. Therefore, the Malay Islamic curriculum can be used as a reference in the development of a national curriculum based on local values and culture.